Demands and Factors Associated to Psychosocial Support of Cancer Patients at Vietnam National Cancer Hospital - Nam Tien Pham; Le Tu Hoang; Nguyen Kim Oanh; Nguyen Khac Liem; Hoang Van Minh (Asian Social Work Journal, 2019)
Cancer patients in Vietnam are increasing exponentially in numbers, with great demands for psychosocial support. This study explored the demands for the psychosocial support of cancer patients at Vietnam National Cancer Hospital and several associated factors. This is a cross-sectional survey, qualitative and quantitative study, and conducted from April to September 2017. This study utilized the structured questionnaire of 418 cancer patients, 8 in-depth interviews and 3 focus group discussions. Results of the study showed that cancer patients have different demands for 6 types of psychosocial support services, specifically: visiting about health and family difficulties (86.1%), providing information on supporting networks for cancer patients (75.7%), psychological counseling and consultation (68.4%), psychotherapy (49.9%), Consultation on self-care for appearance (39.1%), and Consultation on social communication (38.6%). Factors associated to cancer patients’ demands for psychosocial support at Vietnam National Cancer Hospital are gender, the number of treatments, and psychological states. In addition, to improve the quality of life for cancer patients, Vietnam National Cancer Hospital should promote psychosocial support activities for cancer patients, based on associated factors.